Cprp—An Unusual, Repetitive Protein Which Impacts Pleuromutilin Biosynthesis in the Basidiomycete Clitopilus passeckerianus - de Mattos-Shipley, Kate M. J.; Foster, Gary D.; Bailey, Andy M. (Frontiers in Fungal Biology, 2021)
Interrogation of an EST database for Clitopilus passeckerianus identified a putative homolog to the unusual stress response gene from yeast; ddr48, as being upregulated under pleuromutilin production conditions. Silencing of this gene, named cprp, produced a population of transformants which demonstrated significantly reduced pleuromutilin production. Attempts to complement a Saccharomyces cerevisiae ddr48 mutant strain (strain Y16748) with cprp were hampered by the lack of a clearly identifiable mutant phenotype, but interestingly, overexpression of either ddr48 or cprp in S. cerevisiae Y16748 led to a conspicuous and comparable reduction in growth rate. This observation, combined with the known role of DDR48 proteins from a range of fungal species in nutrient starvation and stress responses, raises the possibility that this family of proteins plays a role in triggering oligotrophic growth. Localization studies via the production of a Cprp:GFP fusion protein in C. passeckerianus showed clear localization adjacent to the hyphal septa and, to a lesser extent, cell walls, which is consistent with the identification of DDR48 as a cell wall-associated protein in various yeast species. To our knowledge this is the first study demonstrating that a DDR48-like protein plays a role in the regulation of a secondary metabolite, and represents the first DDR48-like protein from a basidiomycete. Potential homologs can be identified across much of the Dikarya, suggesting that this unusual protein may play a central role in regulating both primary and secondary metabolism in fungi.